Exploring the Factors behind Renewable Energy Consumption in Indonesia: Analyzing the Impact of Corruption and Innovation using ARDL Model - Voumik, Liton Chandra; Akter, Salma; Ridwan, Mohammad; Ridzuan, Abdul Rahim; Pujiati, Amin; Dwi Handayani, Bestari; Keshminder, J. S.; Md Razak, Mohamad Idham (International Journal of Energy Economics and Policy, 2023)
The study examines the relationship between corruption, innovation, and renewable energy consumption in Indonesia using the Marshalian Demand Function (MDF) framework. The research analyzes data from 1984 to 2020 and applies several statistical tests to validate the model’s accuracy. The Autoregressive Distributed Lag (ARDL) approach is applied to evaluate the long and short-term effects of several variables on renewable energy consumption. The study finds that economic growth, number of patents, and FDI positively impact renewable energy consumption in the long term, while urbanization has a negative impact. Trade openness has no long-term impact on renewable energy consumption. In the short term, FDI, corruption, and the number of patents were found to have a significant negative association with renewable energy consumption, while GDP had a significant positive correlation. Diagnostic tests validate the model’s suitability and ensure that it lacks heteroscedasticity and serial correlation. The study emphasizes the importance of encouraging renewable energy consumption and addressing the problems of urbanization and corruption in Indonesia to achieve a more sustainable and energy-efficient future.